Ефективності використання основних фондів та шляхи її покращення - Васильцова, Світлана Олександрівна; Мамедова, Анна Джамаладдинівна; Козюра, Володимир Володимирович (НТУ "ХПІ", 2017)
Сьогодні в Україні окрім загострених політичних ситуацій, присутні ще й значні економічні проблеми. Скорочення власних ресурсів для обладнання виробництва, відсутність бажання інвестувати власні кошти у відтворення підприємств призвели до того, що у розпорядженні значної частини вітчизняних підприємств залишилися практично повністю фізично та морально зношені основні виробничі засоби. Саме тому, проблема визначення ефективності використання основних засобів, та пошук шляхів їх більш продуктивного застосування, є на сьогодні актуальною. Вдале управління основними фондами розглядається як їх дієве використання у виробничому обороті.

Today in Ukraine, besides the acute political situations, there are also significant economic problems. So we can note the degradation of most industrial enterprises, which are already virtually widespread. The small support of enterprises by the state, the reduction of own resources for production equipment, the lack of desire to invest their own funds in the restoration of enterprises led to the fact that at the disposal of a significant part of domestic enterprises remained virtually completely physically and morally worn basic production facilities. That is why the problem of determining the effectiveness of the use of fixed assets, and the search for ways of their more productive use, is today relevant. A significant role in the activity and development of any enterprise is played by the effective use of fixed assets. Due to this the company can achieve the growth of technical level of production, increase of economic and production potential. There are wider opportunities for diversification of production, the release of a new product, which will be more cost-effective and more desirable for consumers. The efficiency of the use of fixed assets also contributes to the production of quality products and the growth of labor productivity.
The effectiveness of the use of fixed assets and ways to improve
Keywords: фондовіддача; технічний стан; виробничі потужності; економічний потенціал; конкурентоспроможність; technical condition; production capacity; economic potential